(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Mass-wasting episodes lead to significant changes in the pressure and temperature regimes within shallow marine sediments and induce variations in the thickness of the gas hydrate stability zone. These variations are marked by vertical migrations of bottom-simulating reflections that typically mark the base of the hydrate zone. Using exploration seismic data from the Offshore Niger Delta, this study presents two examples involving the vertical migration of the base of the gas hydrate stability zones induced by mass-wasting events. The first is related to a slope failure surface along the forelimb of an active thrust-cored anticline with considerable bathymetric relief. Sediment removal has induced both a decrease in overburden pressure and an incursion of cooler temperature flux in strata in the anticline and led to a migration of the base of the gas hydrate stability zone to deeper levels. The second case is related to a recent erosional event that has led to sediment removal along a seafloor channel course. Evidence of ongoing migration of the base of the gas hydrate stability zone to deeper levels is provided by the lateral termination of a BSR along channel wall, its absence beneath the channel bottom and its apparent downward bend close to the channel fringes. Apart from unroofing hydrate systems and releasing free gas into the ocean and possibly the atmosphere, mass-wasting events on the seafloor, represent significant drivers influencing the formation of gas hydrates in shallow subsea sediments and the thickness and depths of the gas hydrate stability zone.